MECHANISMS FOR DETERMINING AND DISTRIBUTING STATE TRANSFERS BY MUNICIPALITIES - D. Ushatova (Trakia Journal of Sciences)
The study aims to present the main characteristics of state transfers for municipal budgets (total subsidy for state-delegated activities, total equalization subsidy, targeted subsidy for capital expenditures, transfer for winter maintenance and snow removal and other current transfers), their purpose and mechanisms for their determination and distribution by municipalities. The specific rules for their spending by the municipalities (targeted and non-targeted) are derived, presenting the introduced control mechanisms on the powers of the local authorities for their spending. The correspondence of the used indicators for distribution of the state transfers by municipalities to the expenditure needs is studied, by making an experimental comparison and grouping of the municipalities according to their revenue capacity for providing these expenses. The changes in the share of the individual types of transfers in relation to GDP, the consolidated fiscal program, the state budget and the municipal budgets are also presented. The general trends for a five-year period are established and the general conclusions are determined, the main one of which is that the local budgets are strongly dependent on the state transfers. Based on the results of the study, some key areas are proposed for improving the distribution mechanisms and development of the regulatory framework in the country.